Minat Individu Menggunakan Smartphone : Studi Empiris Konteks Sistem Mobile Commerce - Putri, Nindia Nur Arifiana (Jurnal Ilmiah Mahasiswa FEB, 2017)
Individual Interest in Using Smartphone : an Empirical Study of the Context of Mobile Commerce System. This study aims to examine numerous factors affecting individual interest in using smartphone in the context of mobile commerce system. This study employs an online questionnaire survey through Google form and takes the samples of students from the Department of Accounting, Faculty of Economics and Business, University of Brawijaya. The numbers of samples which can be processed are 320 respondents. Partial Least Square (PLS) is employed to examine the data of the study. Several hypotheses which are supported by the results of the tests show that the construction on the perceived usefulness and perceived ease of use as well as social influence and attitude affect people’s interest in using smartphones in the context of mobile commerce system. On the other side, the construction on the trust does not affect people’s interest in using smartphones in the context of mobile commerce system.Keywords: Smartphone, Interest in Using, Perceived Usefulness, Perceived Ease of Use, Social Influence, Trust and Attitude.